Belgium : Detailed Assessment of Observance of Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2013)
The Belgian insurance industry was adversely affected by the global financial crisis and continued to confront challenges related to legacy assets and economic uncertainties in Europe. The Belgian authorities have made significant progress in updating the insurance regulatory regime and supervisory practice. The updated regulatory framework has a high level of observance with the Insurance Core Principles (ICPs), supported by robust prudential supervision. The authorities are advised to review current conduct-of-business (CoB) regulation and supervision to strengthen the protection for policyholders.